A Universal Route to Realize Radiative Cooling and Light Management in Photovoltaic Modules. Issue 10 (7th September 2017) - Lu, Yuehui; Chen, Zhicheng; Ai, Ling; Zhang, Xianpeng; Zhang, Jing; Li, Jia; Wang, Weiyan; Tan, Ruiqin; Dai, Ning; Song, Weijie
Abstract : Photovoltaic (PV) modules are not only an opto‐electrical system, but also opto‐thermal one, where the optical, electrical, and thermodynamic domains are strongly coupled. The means to suppress both light and heat losses in PV modules remains undeveloped. Herein, a universal route to realize both radiative cooling and light management via the ultra‐broadband versatile textures is proposed, originating from the interaction with the visible, near‐infrared, and mid‐infrared electromagnetic waves (EMWs) via geometric, diffractive, and subwavelength optical effects. The sol–gel imprinted ultra‐broadband textures exhibited a near‐unity infrared emissivity over 0.96 at the atmospheric window between 8 to 13 μm for radiative cooling, and a solar transmittance and haze above 0.94 and 0.95 at the wavelengths from 350 to 750 nm, respectively, for light management. Applying the ultra‐broadband textures imprinted glass to silicon PV modules as an encapsulant cover, the short‐circuit current and conversion efficiency were increased by 5.12 and 3.13% in relative terms, respectively. The fabrication of such ultra‐broadband versatile textures was photolithography‐free, scalable, and PV industry compatible, which provided a cost‐effective, long‐term durable, and energy‐efficient means to both light and thermal management through ultra‐broadband matter‐EMW interaction not only in PV modules, but also various opto‐electro‐thermal devices. Abstract : Ultra‐broadband versatile textures to realize both radiative cooling and light management are developed by a photolithography‐free and scalable sol–gel imprinting. The imprinted textures have great capabilities in the interaction with MIR EMWs through gradient‐index subwavelength structures and Vis‐NIR waves via geometric and diffractive optical effects, leading to the improved MIR emissivity and Vis‐NIR transparency.